Assurance on CSR reports: impact on the credibility perceptions of non-financial information by bank directors. Issue 5 (5th June 2020) - Quick, Reiner; Inwinkl, Petra
Abstract : Purpose: This paper aims to clarify whether assurance on non-financial corporate social responsibility (CSR) reports impacts the perceptions and decisions of banks as capital providers. The authors investigate the effects of the type of assurance provider and the level of assurance provided on decisions by banks to grant credit, make their own personal investments or recommend share purchases to their customers. The study aims to expand the domain of assurance on CSR reports (CSRR) by taking up a call by Cohen and Simnett (2015), who ask for behavioral research on how non-financial report's intended users interpret and react to assurance. Design/methodology/approach: The paper is based on an experiment case on a fictitious company with a 2 × 2 + 1 between-subjects design. To overcome concerns regarding external validity and to prove results in a real-world setting, the authors selected German bank directors as subjects due to the extremely high relevance of banks to the German economy. The authors investigated the perceptions of 69 bank directors and analyzed the influence of CSR assurance on their decisions. Findings: The findings suggest that assurance positively influences confidence in CSRR and that, consequently, bankers are more likely to make favorable decisions toward the reporting companies, such as approving applications for credit, investing themselves in the company or recommending the purchase of shares to their clients. These effects are stronger when an accounting firm provides the assurance and when the assurance level is reasonable rather than limited. Research limitations/implications: The arguments presented are, strictly speaking, limited to the case in the experiment and the views held by the bank directors at the time the authors sent out the questionnaires. Moreover, the cell sizes are quite small. Nevertheless, the authors were able to find highly significant results. Practical implications: The main implication of the paper is that the purchase of CSRR assurance services has a positive effect on bank directors' perceptions and decisions. They favor the provision of such services by accounting firms and they prefer a reasonable assurance level. Thus, it can be concluded that bank directors perceive quality differences between assurance providers, are able to recognize the difference between reasonable and limited assurance and that the related information is relevant for their decisions. Originality/value: This paper fulfils an identified need to study the influence of CSRR assurance on decisions by bank directors. The observation of a high decisions-usefulness of CSRR assurance suggests that regulators should consider mandating some form of assurance on non-financial reports throughout the EU member states.